Effect of medicinal plant extracts on seed germination and seed associated mycoflora of wheat (Triticum aestivum L.) - Mahal, MF; Akter, MS (Journal of Bio-Science, 2019)
The experiment was carried to evaluate the efficacy of five different plant extracts i.e. Adhatida vasica, Tagetes patula, Vinca rosea, Lowsonia alba and Andrographis paniculuta on seed germination, vigor index and seed borne and seed associated mycoflora of wheat varieties viz. Sourav and Prodip in in vitro condition. Seed health test of the collected wheat seed revealed that the seed was associated with six different fungi viz. Bipolaris sorokiniana, Fusarium sp., Aspergillus spp., Trichoderma viride, Penicillium sp. and Rhizopus sp. Wheat seeds were treated by dipping separately into different plant extracts of 1:1, 1:2 and 1:3 dilutions. Among the plant extracts, Lowsonia alba leaf extract was observed most effective followed by A. vasica, T. patula, V. rosea and A. paniculuta in reducing seed borne and seed associated mycoflora and also increased the germination rate and vigor index. J. bio-sci. 27: 23-30, 2019